AIR CONDITIONING LOAD AND ANALYSIS CALCULATION OF AIR DISTRIBUTION IN VEHICLE CABINS BRIDGE MAINTENANCE INSPECTION - Mulyono, Mulyono; Sadewa, Maulana; Soegiharto, Achmad Fauzan Hery; Restu, Firdausa Retnaning (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Cabin comfort is essential for an inspector to work focusly and produce valid data in a bridge maintenance vehicle. The use of an air conditioner (AC) in the cabin of this vehicle is a concern for the inspector's comfort while supervising the bridge. Choosing an inappropriate AC can result in excessive energy consumption or inadequate thermal comfort. Furthermore, the transparent windows and windshields of glass elevate the temperature and allow sunlight to invade the room. Consequently, it intensifies the cooling demand. Considering this situation, this study focuses on calculating the cooling load in the cabin and simulating the thermal performance using computational fluid dynamics (CFD). The simulations were conducted using Ansys 2023 software, with a runtime of 4 minutes and 2,400 iterations. It is to achieve a cabin temperature within the comfort range of 22–26°C. The cabin is designed for two inspectors. At an airflow velocity of 3 m/s, the simulation yielded a maximum temperature of 40°C and a minimum of 21.13°C. Reducing the airflow to 2 m/s resulted in a range of comfortable temperatures for the cabin. In conclusion, the simulation results fulfill the criteria and confirm that an airflow velocity of 2 m/s is sufficient to maintain the comfortable temperature in the cabin.